استئجار الارحام دراسة مقارنة بین الشریعة الإسلامیة والقانون الوضعي - غندوفة, ربيعة (University of eloued جامعة الوادي, 2014)
يعالج البحث موضوع استئجار الأرحام الذي يعتبر من أبرز الوسائل الحديثة في الإنجاب الصناعي، ويعالج مشكلة لدى الكثيرين ممن يعانون العقم، والحرمان من الأبناء، فقد دفع ذلك الكثير إليها والتساؤل عن شرعيتها، مع وجود بعض الفتاوى التي أباحتها، وهنا كان لابد من الوقوف على هذه النازلة ومعرفة رأي علماء الشريعة الإسلامية فيها والقوانين الوضعية سواء العربية منها أو الغربية، وبناء على ما سبق، فقد تناولنا الموضوع بالدراسة والذي توصلنا فيه إلى حرمة استئجار الأرحام بجميع صوره في الشريعة الإسلامية أما القوانين الوضعية فتباينت ازاء هذه النازلة بين مجرم ومبيح ، ونتج عنها العديد من المفاسد الأسرية والأخلاقية والنفسية. The Research-Paper deals with the topic of The Wombs' Trade; which is considered as a prominent modem tool in The Industrial Procreation and it treats the problem of many infertile and deprived people from children; this pushed them to look for its Iegitimacy within some existed Legal Opinions that have legitimated it; soit is necessary to stand on this Falling and knowing the Jurisprudents' Approach about it , besicles The Common Laws either Arabie or Western ones. Through what is mentioned before; The Research- Paper is divided into three chapters: in the first chapter we dealt with The Wombs' Renting and The Artificial Endogamy, in the first section we treated The Essence of The Wombs' Renting, in the second we mentioned The Artificial Endogamy and its relationship with the W ombs' Renting. The second chapter entitled by the Islamic Legislation and the Common Laws' point of views in Wombs' Renting ; in the first section, we illustrated the Islamic Legislation Rule about the Renting of Wombs, the second section clarified The Wombs' Renting in The Common Laws. The third chapter spoke about The Deficiency resulted " from W ombs' Renting and we mentioned in the first section The Deficiencies that families could face due to the Wombs' Renting; while the second section included The Ethical and Psychological Deficiencies when Renting Wombs. At Iast we arrived to a several results.
شريعة وقانون
Keywords: استئجار/ الارحام/القانون الوضعي; Hire / Surrogacy / Positive Law